An analysis of the extent to which employees of post-80s and 90s in China can be motivated by financial and non-financial rewards. - YU, JIAYING (2020)
As Chinese post-80s and 90s employees whose values of job motivation, rewards and satisfaction have huge difference with workforce of other generation due to special social context they have experienced, it is significant to examine factors that motivate them effectively. There are three main research focus, the first focus is to find out factors that demotivate and dissatisfy them; the second focus is to identify their preference of rewards within financial and non-financial rewards; the last focus is to explore factors that influence the retention of this special cohort.